FINANCIAL ECOSYSTEM OF GLOBAL ECONOMIC INTEGRATION (INNOVATIVE ECONOMY, 2025)
Ivashchuk I.O., Uhryn B.V. FINANCIAL ECOSYSTEM OF GLOBAL ECONOMIC INTEGRATIONPurpose. The aim of the article is substantiation of the formation of the financial ecosystem of global economic integration as its multi-level environment and identification of its characteristics.Methodology of research. A set of general scientific and special research methods was used to achieve the stated goal, in particular: the method of system analysis was used to form the theoretical and methodological basis of the study; methods of generalization, induction, deduction – to formulate conclusions and generalizations; analysis and synthesis – to identify the characteristics and models of the financial ecosystem of global economic integration; method of comparative analysis – to identify the features of global integration of economies. The empirical part of the study was based on the use of statistical and econometric methods, in particular, cluster analysis, correlation and regression analysis. Findings. It is substantiated that in the conditions of growing global interdependence of countries, a new financial ecosystem is being formed. The evolution of globalization processes and the growth of openness of national economies are confirmed. A comprehensive approach to understanding the financial ecosystem of global economic integration is proposed and its main components are identified. The differences between economies in terms of the level of globalization are determined and it is established that global integration is not the only determinant of economic development; therefore it is advisable to take into account the influence of its individual components. A system of characteristics of the financial ecosystem of global economic integration is proposed and a correlation matrix is ​​constructed in order to identify the relationships between them. A multifactor analysis toolkit was used to assess the impact of a set of factors on the economic well-being of economies. Using cluster analysis methods, clusters of economies were formed according to the characteristics of the financial ecosystem of global economic integration. Models of financial ecosystems of countries' integration into the global economy are proposed.Originality. The conceptual approach to the interpretation of the financial ecosystem of global economic integration as a multi-level dynamic environment and the isolation of its components is substantiated. The work identifies key characteristics of the financial ecosystem of global economic integration, taking into account the level of involvement of economies in global processes. The identification of the impact of the characteristics of the financial ecosystem on the social and economic development of economies, in particular on the level of GDP per capita, has been further developed. Based on the relationship between the levels of financial globalization de facto and de jure, models of financial ecosystems of integration are proposed.Practical value. The results of the study can be used in developing strategies for integrating national economies into the global economic space; to assess the level of integration of countries and determine priority areas of financial policy; as well as in scientific and educational activities.Key words: globalization, global economic integration, economic development, financial ecosystem, Globalization Index, trade globalization, financial globalization, investments, financial flows, financial openness.
Keywords: globalization; global economic integration; economic development; financial ecosystem; Globalization Index; trade globalization; financial globalization; investments; financial flows; financial openness